Analysis of Illocutionary Act in The Movie “IT” (2017) English Subtitle - Alimah, Aulia Ulfatul (Melati Institute, 2024)
This research delves into the comprehensive analysis of illocutionary acts within the context of the movie “IT” (2017). By closely examining the film’s script, we identify five distinct categories of illocutionary acts: representative, directive, commissive, expressive, and declarative. Notably, directive acts emerge as the most prevalent, constituting 35% of the total occurrences. Our study contributes valuable insights to the understanding of speech acts in cinematic dialogue, with potential applications in linguistics, education, and even scriptwriting.